2010
DOI: 10.1097/01.nur.0000348967.04990.99
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Nurses and Physicians When Making End-of-Life Decisions in Intensive Care Units

Abstract: Purpose/Objectives: The purpose of the study was to describe the relationship between anger, spirituality, and subjective and objective indices of heart disease risk among a convenience sample of nontraditional college students at a small private university in South Texas. Nontraditional college students are defined as slightly older commuter students who balance family, work, and school schedules.Research Hypothesis/Question(s):(1) What are the risk factors, level of anger, and spirituality of nontraditional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(56 citation statements)
references
References 0 publications
0
51
0
5
Order By: Relevance
“…Thus, this issue was a growing problem at this time, acknowledged by ICU nurses but perhaps not yet on the agenda among most ICU physicians in Europe. However, today all ICU health care professionals report that the transition from curative medical care to EOL care is the most problematic stage in providing EOL care (Coombs et al, 2012;McAndrew and Leske, 2014).…”
Section: A Short Lock Backmentioning
confidence: 99%
“…Thus, this issue was a growing problem at this time, acknowledged by ICU nurses but perhaps not yet on the agenda among most ICU physicians in Europe. However, today all ICU health care professionals report that the transition from curative medical care to EOL care is the most problematic stage in providing EOL care (Coombs et al, 2012;McAndrew and Leske, 2014).…”
Section: A Short Lock Backmentioning
confidence: 99%
“…21,29,47,52,60 Nurses were more likely to report physician communication as a cause of a medication error when they reported higher levels of moral distress. 42 The challenges of working within an interdisciplinary team and consequential poor communication and collaboration were described in many studies 11,22,30,31,49,53,56,57 Nurses reported that medical values take priority over nursing values within the organizations they practice. 43,53 Unprofessional behavior of physician colleagues is also described by nurses as a barrier to addressing ethical conflict in patient care.…”
Section: Factors That Contribute To Moral Distressmentioning
confidence: 99%
“…38,42,47,52,59 Patients and families may experience poor communication, prolonged deaths, and inadequate nursing support. 22,30,31,48,49,53,56,57,59 There is a weak positive relationship between moral distress and burnout. 32 Elements of nurse burnout including depersonalization and emotional exhaustion are both negatively correlated with job satisfaction.…”
Section: Moral Decision-making and Advocacymentioning
confidence: 99%
“…It is well documented that communication challenges during decisions about life-sustaining treatments are a source of moral distress 2 4. Inadequate nurse–physician collaboration and healthcare professional conflict can lead to inadequate nurse involvement in decision-making processes,3and undermine patient and family end-of-life care 5. Given the critical importance of nurse–physician collaborative practice, the purpose of the study by Laurent and colleagues1 was to describe the experiences of nurses and doctors when making end-of-life decisions in the ICU.…”
Section: Contextmentioning
confidence: 99%
“…Positive end-of-life experiences may provide valuable insights about aspects that facilitate smooth end-of-life transitions and enhance interprofessional communication 3. Studying the dynamic intersection among healthcare professionals, patients and family members within the ICU and various organisational settings is required to advance the science.…”
Section: Commentarymentioning
confidence: 99%